Across the desert - Bowling, Dusti (Little, Brown and Company, 2021)
While using a public library computer to find help for her mother who is addicted to pain medicine, twelve-year-old Jolene witnesses a friend's live-streamed crash-landing in the Arizona desert and embarks on a journey to rescue her.